Metal Organic Frameworks of CPL-4 and CPL-5 Synthesis and Characterization under Magnetic Fields - Moondra Zubir; Hafni Indriati Nasution; Minda Shafina Syafei (Universitas Negeri Medan, 2019)
CPL-4 and CPL-5 were synthesized with used 2,3 pyrazine dicarboxylic acid as main ligand , 4,4’-azopyridine(Apy) as linker ligand for CPL-4 and 1,2-di-(4-pyridil)ethylene(Bpe) for CPL-5 in water-ethanol(1:1) and temperature 250C. Three methods used in various reaction time and dropping method to metal ion with no stir treatment and also stirring or shaking treatment. CPL-4 have no magnetic field effect shows same XRD pattern in all synthesis method. Otherwise, CPL-5 with used method#03 shows different XRD pattern in 0T and 6T. By changing concentration of Cu2+ to 0.02 M, 6T crystal also shown different XRD pattern if compared with 6T crystal with 2 hours to 1 hours reaction time. It indicate of changing reaction between Hpzdc and Bpe with metal ion or reactivity both of ligand with metal ion induce different route under 6T. This process may effect to new crystal structure during synthesis in 6T..